Financial Globalization and the Emerging Market Economy. - Das, Dilip K. (Routledge studies in the modern world economy., 2004)
Dilip Das examines the impact of ever increasing financial globalization on emerging market economies, both in the former communist countries of Eastern Europe and the developing world in general.